Effects of confining pressure and loading direction on the mechanical behavior of schist with high content and aggregation degree of mica - Qiliang Liu; Jing Xiang; Xiaomeng Yin; Kun Song (PLoS ONE, 2026)
This article focuses on the mechanical anisotropy of the schist with high content and aggregation degree of mica, which are prone to causing local collapse, large deformation, and support failure in tunnel engineering. The fabric characteristics of rock and the response of mechanical properties to confining pressure and loading direction was emphatically explored by micro tests and compression tests with confining pressures ranging from 0 to 20 MPa. Micro tests reveal that the flaky micas are highly aggregated and directionally arranged in the “matrix” composed of granular minerals and directional cracks are developed along the cleavage or the boundaries of mica. Mechanical tests indicate that the peak strength and elastic modulus of schist subjected to uniaxial compression vary in a shoulder form and U-shaped form with the orientation angle α , respectively. The confining pressure σ 3 nonlinearly weakens the anisotropy of schist and the transition of rock behavior from anisotropic to isotropic occurs at a critical confining pressure. Moreover, the critical ratio has a negative correlation with the most representative uniaxial compressive strength and strength anisotropy degree under uniaxial compression. As σ 3 increases, the failure mode changes from tension and shear composite to pure shear at α = 90° and from splitting and shear composite to plastic kinking at α = 0°, while maintains sliding shear at α = 30°. However, under the low σ 3 , the tested schist is different from the schist with low content and aggregation degree of mica in the failure mode at α = 0° and 30°, which is attributed to the differences in the microstructures of two schist. These findings yield an in-depth understanding of the mechanical behavior of foliated rocks and offer important references for the stability evaluation and support design of tunnel surrounding rock.